PENGARUH STRUKTUR MODAL DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PULP AND PAPER YANG LISTING DI BURSA EFEK INDONESIA TAHUN 2011-2015 - Guta, Rafiqa Risfiana; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study aims to examine the persial and simultaneous influence of capital structure and firm size on firm value. Where independent variable in this research is capital structure and company size while dependent variable is company value. The sample used is secondary data derived from the financial statements of pulp and paper companies listed on the Indonesia Stock Exchange (IDX) period 2011 to 2015.This study uses secondary data from the company's financial statements. Samples and sampling using purposive sampling technique. Data analysis using multiple linear regression analysis, t test, F test, and test of coefficient of determination. Data analysis using multiple linear regression analysis with SPSS 20.The results of this study indicate that the variable of capital structure in persial (t test) does not affect the company value, while the firm size variables affect the value of the company in the pulp and paper companies listed on the Indonesia Stock Exchange. The simultaneous test results (F) show the effect of capital structure variable and firm size on firm value on pulp and paper companies listed in Indonesia Stock Exchange.Keywords: capital structure, firm size and company value